An Applied, Judicial, Analytical and Questioned Study What It Is - Its Characteristics - Its Conditions - Its Elements - The Defenses That the Sponsor May Uphold67 - Sadam Mohammad Ali AlHawamdeh, (International Journal of Advanced Science and Technology, 2020)
Through our reference to the articles of the Jordanian Civil Law, it is devoid of a legal text confirming this, but from our humble point of view, since the civil lawsuit or the executive lawsuit belongs to the litigants (the creditor - the debtor), it is permissible for the creditor to exempt and exclude the guarantor from the debt claimed by the original debtor Before the court or enforcement departments, the creditor has the right to retain the right to claim payment on the original debtor, and we have measured that, as confirmed by the Jordanian Civil Code in one of its texts No. (967), which states the following: “1 - The creditor has the right to demand the principal or the guarantor or both of them - 2 And if the guarantor has a guarantor, then the creditor has a claim from either of them 3 - Provided that his claim to one of them does not waive his right to claim the others.